Penggunaan Metode Bermain Peran untuk Mengembangkan Kemampuan Sosial Emosional Anak Usia Dini Kelompok B di TK Darma Wanita Persatuan 2 Bayuglugur Situbondo - Yati Nur Hafiyah; Mohammad Zaini (HMPS PIAUD FTIK IAIN Jember, 2022)
Early childhood education plays an important role in social and emotional development. The need for an educational method that makes learning more interesting and certainly effective. The right method used in early childhood is the role-playing method. This study aims to determine 1) the use of the role-playing method 2) the advantages and disadvantages of the role-playing method 3) The results of the use of the role-playing method. This study uses a descriptive qualitative approach and data collection methods using observation, interviews, and documentation. Data analysis uses data condensation, Data display, Drawing, and Verifying Conclusions. The validity of the data using source triangulation and technical triangulation. This research concludes 1) The use of the role-playing method in which there are several steps and the role-playing method used is as a police officer with the theme